THE WIKE PHENOMENON, POLITICAL DUALISM AND TRANS-PARTISAN HEGEMONY IN CONTEMPORARY NIGERIA: THE RIVERS STATE EXPERIENCE - Christopher Barisi Barigbon; Tambari Adooh; Barikuma Lazarus Ndaage (International Journal of Business, Law and Political Science, 2026)
Objective: This paper examines a new trend in Nigerian politics that is defined by the increasing power of elite players who operate outside of official party lines. The paper examines how political players maintain their relevance in the face of rival party formations, the institutional framework that permits this kind of dual positioning, and the consequences of these dynamics for Nigerian democratic governance, party ideology, and accountability. Method: The study uses a qualitative and descriptive research design based on media reports, documentary sources, and previously published literature on Nigerian party politics. It is grounded in elite theory and patron-client theory. Results: The results show that through elite broking, institutional penetration, patronage networks, electoral coordination, and discursive control over political narratives, dominant political actors have been able to simultaneously influence both ruling and opposition parties due to weak party institutions, patronage-driven politics, and the personalisation of power. Novelty: The paper conceptualizes "political dualism" and "trans-partisan hegemony" as analytical frameworks for comprehending the growing convergence between ruling and opposition political structures in Nigeria's Fourth Republic, using Nyesom Wike's political trajectory as a case study. The study comes to the conclusion that the "Wike phenomenon" is a reflection of a larger structural situation in which formal party systems are increasingly replaced by transpartisan elite structures as a means of exercising substantive political authority.